Tantangan Guru dalam Memantau Perkembangan Pemahaman Matematika Siswa MTs Darul Aziz - Hafiz Multazam Azhar; Imam Sujarwo (Yayasan Al-Afif, 2025)
This research aims to explore the challenges faced by teachers at MTs Darul Aziz in monitoring students' mathematical understanding. The study employs a qualitative descriptive approach, utilizing interviews, observations, and documentation as data collection methods. The findings reveal several interrelated obstacles: students' passive attitude, limited class time, differences in academic ability, inadequate use of formative assessments, lack of systematic documentation of learning progress, and the influence of social dynamics in the classroom. These challenges hinder teachers' ability to accurately assess students' deep understanding of mathematical concepts, particularly when applying concepts to varying problem sets. The study concludes that there is a need for more adaptive and creative strategies in monitoring student understanding, including regular formative assessments, differentiated learning, and structured documentation. These improvements would enable teachers to provide more accurate evaluations, increase student engagement, and enhance the effectiveness of mathematical teaching.